(untitled) (Canadian Dermatology Today, 2021)
Dr. Diana Diao is a dermatologist and a Clinical Instructor in the Department of Dermatology and Skin Science at the University of British Columbia. She practices both medical and cosmetic dermatology at Pacific Derm in Vancouver, and also serves as a clinical trials sub-investigator. She is a consulting dermatologist at St. Paul’s Hospital in Vancouver. She completed her medical school and dermatology residency training at the University of British Columbia.